Resolution of Conflict and Human Human Rights Violations in Papua - Melkias Hetharia; Josner Simanjuntak (International Journal of Social Service and Research, 2025)
The conflict in Papua is a long-standing issue and involves various aspects, including human rights. Numerous human rights violations have fueled Papuan distrust of the central government. The dominant repressive approach often worsens relations between the community and the state. Under these circumstances, a reconciliation approach becomes an important alternative for conflict resolution. This study aims to formulate a sustainable reconciliation-based conflict resolution strategy in Papua. This study employed qualitative research methods with a descriptive-analytical approach. The data collection technique used was a literature review. The data analysis techniques used were data reduction, data presentation, and conclusion drawing. The results indicate that the conflict and human rights violations in Papua are multidimensional problems influenced by development inequality, marginalization of indigenous Papuans, limited participation in decision-making, and the dominance of a less-than-humanistic security approach. These conditions have led to injustice, undermined public trust in the state, and prolonged the conflict, resulting in violence, humanitarian crises, and disruptions to social life. Therefore, resolving the Papuan conflict requires an approach that focuses not only on security but also on justice, dialogue, and social restoration.